A randomized controlled and long‐term linaclotide study of irritable bowel syndrome with constipation patients in Japan. Issue 12 (22nd August 2018) - Fukudo, Shin; Miwa, Hiroto; Nakajima, Atsushi; Haruma, Ken; Kosako, Masanori; Nakagawa, Ayako; Akiho, Hiraku; Yamaguchi, Yusuke; Johnston, Jeffrey M.; Currie, Mark; Kinoshita, Yoshikazu
Abstract: Background: Clinical testing was required to verify the effect of linaclotide 0.5 mg/d in patients with irritable bowel syndrome with constipation (IBS‐C) in Japan. Methods: This was a randomized, double‐blind, placebo‐controlled (Part 1) and long‐term, open‐label extension (Part 2) study of linaclotide at 60 hospitals and clinics in Japan. Patients with IBS‐C diagnosed using Rome III criteria (n = 500) were randomly assigned to linaclotide 0.5 mg (n = 249) or placebo (n = 251) for a 12‐week treatment period followed by open‐label treatment with linaclotide (n = 324) for an additional 40 weeks. The primary endpoints were the responder rate of global improvement of IBS symptoms and complete spontaneous bowel movement (CSBM) during 12 weeks. The secondary endpoints included responder rates of SBM and abdominal pain/discomfort relief. Key Results: Part 1: The responder rates for global improvement and for CSBM frequency were significantly higher for linaclotide compared to placebo ( P < 0.001). Secondary endpoints including responder rates for SBM and abdominal pain/discomfort relief in the linaclotide group were also significantly greater than those in the placebo group. Part 2: Patients switched from placebo to linaclotide showed similar responder rates for global improvement and CSBM frequency to those in patients who continued to receive linaclotide, supporting sustained efficacy. Diarrhea was seen in 14.5% of patients; all cases were mild or moderate. Conclusions and Inferences: This study suggests that a linaclotide dose of 0.5 mg is effective and safe for IBS‐C patients in Japan. Abstract : Linaclotide has been approved in western countries for IBS with constipation (IBS‐C) at a dose of 0.29 mg. A previous phase II trial in Japan reported that 0.5 mg/d of linaclotide was the most effective dose in IBS‐C patients. This phase III trial in IBS‐C patients in Japan revealed that 0.5 mg/d of linaclotide was effective on global improvement (A), complete spontaneous bowel movement (B), and abdominal pain/discomfort with enough safety.